From soft to superhard: fifty years of experiments on cold-compressed graphite - Wang, Y.; Lee, K.K.M. (Сверхтвердые материалы, 2012)
In recent years there have been numerous computational studies predicting the nature of cold-compressed graphite yielding a proverbial alphabet soup of carbon structures (e.g., bct-C4, K4-, M-, H-, R-, S-, T-, W- and Z-carbon). Although theoretical methods have improved, the inherent nature of graphite (i.e., low-Z) and the subsequent room-temperature, high-pressure phase transition (i.e., low symmetry, nanocrystalline and sluggish), make experimental measurements difficult to execute and interpret even with the current technology of 3rd generation synchrotron sources. The room-temperature, high-pressure phase transition of graphite has been detected by numerous kinds of experiments over the past fifty years, such as electrical resistance measurements, optical microscopy, X-ray diffraction, inelastic X-ray scattering, and Raman spectroscopy. However, the identification and characterization of high-pressure graphite is replete with controversy since its discovery more than fifty years ago. Recent experiments confirm that this phase has a monoclinic structure, consistent with the M-carbon phase predicted by theoretical computations. Meanwhile, experiments demonstrate that the phase transition is sluggish and kinetics is important in discerning the phase boundary. Additionally, the post-graphite phase appears to be superhard with hardness comparable to that of diamond. В останні роки було проведено велику кількість чисельних досліджень, що прогнозують основні властивості графіту, підданого стисненню при кімнатній температурі, в результаті чого виникає загальновідомий “алфавітний суп” з вуглецевих структур (наприклад, bct-C₄, K₄-, M- , H-, R-, S-, T-, W-і Z-вуглець). Тоді як теоретичні методи стали більш досконалими, природа, притаманна графіту (тобто низьке Z), і подальший фазовий перехід при кімнатній температурі і високому тиску (низькосиметричний, нанокристалічний і млявий) роблять експериментальні вимірювання важко здійсненними і їх складно інтерпретувати навіть із застосуванням сучасної технології, що використовує 3-е покоління синхротронних джерел. За минулі 50 років фазовий перехід графіту при кімнатній температурі і високому тиску був виявлений багатьма видами експериментів, таких як вимірювання електроопору, оптична мікроскопія, дифракція рентгенівських променів, непружне розсіювання рентгенівських променів і раманівська спектроскопія. Однак з дня його відкриття більше 50 років тому ідентифікація та отримані характеристики графіту високого тиску повні суперечностей. Недавні експерименти підтверджують, що ця фаза має моноклинну структуру, узгоджується з М-вуглецевої фазою, передбаченою теоретичними розрахунками. Поки експерименти демонструють, що фазовий перехід є повільним, а при розпізнаванні фазових границь важливе значення має кінетика процесу. Крім того, пост-графітова фаза є надтвердою, за твердістю близькою до алмазу. В последние годы было проведено большое количество численных исследований, предсказывающих основные свойства графита, подвергнутого сжатию при комнатной температуре, в результате чего возникает пресловутый “алфавитный суп” из углеродных структур (например, bct-C₄, K₄-, M-, H-, R-, S-, T-, W- и Z-углерод). В то время как теоретические методы стали более совершенными, природа, присущая графиту (т. е. низкое Z), и последующий фазовый переход при комнатной температуре и высоком давлении (низкосимметричный, нанокристаллический и вялый) делают экспериментальные измерения трудно выполнимыми и их сложно интерпретировать даже с применением современной технологии, использующей 3-е поколение синхротронных источников. За прошедшие 50 лет фазовый переход графита при комнатной температуре и высоком давлении был обнаружен многими видами экспериментов, таких как измерения электросопротивления, оптическая микроскопия, дифракция рентгеновских лучей, неупругое рассеяние рентгеновских лучей и рамановская спектроскопия.. Однако со дня его открытия более 50 лет назад идентификация и полученные характеристики графита высокого давления полны противоречий. Недавние эксперименты подтверждают, что эта фаза имеет моноклинную структуру, согласующуюся с М-углеродной фазой, предсказанной теоретическими расчетами. Пока эксперименты демонстрируют, что фазовый переход является медленным, а при распознавании фазовых границ важное значение имеет кинетика процесса. Кроме того, пост-графитовая фаза является сверхтвердой, по твердости близкой алмазу.